Dynamic Fluid E-Module with STEM Approach to Stimulate HOTS of High School Students in Distance Learning - Suyatna, Agus; Viyanti, Viyanti; Sestika, Sestika (Jurnal Pendidikan MIPA, 2020)
Efforts to grow HOTS in high school students are very important to provide for 21st century skills and the demands of the industrial revolution era 4.0. One of these efforts is by providing teaching materials that can stimulate HOTS. This research was aimed to develop a fluid e-module with a valid, effective, and practical STEM approach to stimulate HOTS for high school students. We used the ADDIE R & D model research method which consists of five stages, which are analysis, design, development, implementation, and evaluation. The developed e-module product was examined for validity, legibility, effectiveness, and practicality tests. The e-module validity test was conducted by five physics learning experts using a Likert scale questionnaire instrument and analyzed using the percentage technique. The legibility test was conducted by five high school students using a Likert scale questionnaire. The practicality test was carried out in senior high schools in Bandar Lampung using a Likert scale questionnaire. The effectiveness test was carried out using the one-group pretest-posttest design. The effectiveness of the dynamic fluid e-module in stimulating HOTS was determined based on the N-gain value and the difference between the pretest and posttest means. The data were analyzed using Wilcoxon Sign Rank test. The results showed that the developed dynamic fluid e-module with the STEM approach was valid, effective, and practical to stimulate HOTS in distance learning in high school. Keywords: e-module, STEM approach, stimulating HOTS, dynamic fluid.  DOI: http://dx.doi.org/10.23960/jpmipa/v21i2.pp132-145